WATCLUST: a tool for improving the design of drugs based on protein-water interactions - Lopez, Elias Daniel (2015)
Motivation: Water molecules are key players for protein folding and function. On the protein surface, water is not placed randomly, but display instead a particular structure evidenced by the presence of specific water sites (WS). These WS can be derived and characterized using explicit water Molecular Dynamics simulations, providing useful information for ligand binding prediction and design. Here we present WATCLUST, a WS determination and analysis tool running on the VMD platform. The tool also allows direct transfer of the WS information to Autodock program to perform biased docking. Availability and implementation: The WATCLUST plugin and documentation are freely available at http://sbg.qb.fcen.uba.ar/watclust/.